Syiling Emas Enterprise / Hisyam Abdul Ghani ... [et al.] - Abdul Ghani, Hisyam; Hamzah, Noraini; Jamil, Juliana; Fuad, Siti Farisah; Mustapha, Siti Khatuah; Roslan, Noryani (Malaysian Entrepreneurship Development Centre (MEDEC), 2002)
Syiling Emas Enterprise is a coin stockist company, which provides coin exchange services to entrepreneurs, lis estahUshmeut is to solve the problems faced by he entrepreneurs who have little amount of coins. Shortage of coins will affect the running of such business